2006
DOI: 10.1002/bit.21141
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid and manganese supplementation modulates the glycosylation state of erythropoietin in a CHO culture system

Abstract: The manufacture of secreted proteins is complicated by the need for both high levels of expression and appropriate processing of the nascent polypeptide. For glycoproteins, such as erythropoietin (EPO), posttranslational processing involves the addition of oligosaccharide chains. We initially noted that a subset of the amino acids present in the cell culture media had become depleted by cellular metabolism during the last harvest cycle in our batch fed system and hypothesized that by supplementing these nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 39 publications
3
85
1
Order By: Relevance
“…Manganese plays a fundamental role in the glycosylation pathway, as shown by many authors 23,52,56 . It determines the levels of various oligosaccharide species including high mannose, galactosylated, fucosylated and sialylated proteins.…”
Section: Glycosylationmentioning
confidence: 94%
See 4 more Smart Citations
“…Manganese plays a fundamental role in the glycosylation pathway, as shown by many authors 23,52,56 . It determines the levels of various oligosaccharide species including high mannose, galactosylated, fucosylated and sialylated proteins.…”
Section: Glycosylationmentioning
confidence: 94%
“…Given its potential, protein quality tuning by media design gained much interest in the last few years. Crowell et al 23 described in 2007 how manganese supplementation modulated the glycosylation state of erythropoeitin (EPO) in a CHO cell culture. These findings are based on early experiments by Kaufman et al who observed the pivotal role of manganese in the secretory pathway of complex N-linked and O-linked oligosaccharides, thus suggesting the unique requirement for manganese 56 .…”
Section: Chapter 2 the Potential Of Media To Enhance Protein Qualitymentioning
confidence: 99%
See 3 more Smart Citations